Public Knowledge, Attitude, and Practice toward COVID-19 Prevention: a Literature Review - Estriana Murni Setiawati (Universitas 'Aisyiyah Yogyakarta, 2021)
This study aims to review the public knowledge, attitude, and practice toward COVID-19 prevention. Pubmed, Ebscho, and Google Scholar database were used as Data sources of this review. PICOST problem analysis guide was applied to find good journals. The journals used in this study were published between 2020 and 2021. Overall of the public knowledge, attitude, and practice toward COVID-19 prevention were varied and synthesized. Articles’ comparisons were complicated because the knowledge, attitude, and practice results were used at various formulas. A more direct intervention is needed to enhance public knowledge, attitude, and practice toward COVID-19 Prevention. Increasing and maintaining good public knowledge, attitude, and practice toward COVID-19 prevention are crucial to cut off the spread of COVID-19.Keywords: Knowledge, Attitude, Practice, and COVID-19 prevention